Integrated geophysical models for interpretations of heterogeneous subsurface environments - Muhammad Taqiuddin Zakaria,; Nur Azwin Ismail,; Nordiana Mohd Muztaza,; Mohd Faiz Mohamad Zaki, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Near-surface characterization can be vulnerable to misinterpretation due to limited resolution and methodological limitations. Validation from different parameters is necessary to substantiate the results and reduce errors during interpretations. This research aims to develop an alternative integrated method of a 2-D cross-plot model to enhance subsurface interpretations based on the model’s criteria, resulting in better geological interpretation. Geophysical methods such as electrical resistivity and seismic refraction are utilized in a test model and a case study area to observe the capabilities of the integrated method approach. The goal of this study was to cluster two or more different parameters into a single model for a direct presentation of the subsurface model. This includes the characterization of subsurface properties, data integration using cross-plot analysis, and the development of a 2-D cross-plot model. This method visually represents the relationship between two or more attributes, allowing for the identification of anomalies. In the test model, the lithology consists of sandy silt derived from granitic residual soil, whereas in the case study model, it was dominated by weathered granitic residual soil with the presence of saturated zones. The 2-D cross-plot model provides a comprehensive interpretation where Quadrant, Q1 shows the vulnerable zones for sliding mass bodies. The plane weakness was successfully identified based on the cross-plot model as the weathered zone, and subsurface features were determined. The estimated volume of mass movement was successfully calculated for the case study area based on the determination of the sliding plane. The integrated method of cross-plot analysis along with the development of 2-D cross-plot models proves to be an informative approach for subsurface characterization and enhances subsurface imaging.